2020
DOI: 10.1016/j.celrep.2020.107540
|View full text |Cite
|
Sign up to set email alerts
|

GDE2-Dependent Activation of Canonical Wnt Signaling in Neurons Regulates Oligodendrocyte Maturation

Abstract: Highlights d GDE2 is expressed in neurons and a subset of oligodendrocytes d Loss of neuronal GDE2 delays oligodendrocyte maturation and impairs myelination d GDE2 stimulates canonical Wnt signaling in neurons, which releases phosphacan d Neuronally derived phosphacan promotes oligodendrocyte maturation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 70 publications
2
45
0
Order By: Relevance
“…Previous studies have shown that Cre-dependent excision of exon 11 results in the complete loss of GDE2 protein expression, validating this strategy to be an effective method to ablate cellular function of GDE2 in vivo [32][33][34] . For this study, we utilized an established inducible mouse line (PDGFαR-CreER) where administration of 4 hydroxytamoxifen (4-HT) induces active Cre recombinase expression under the control of Platelet derived growth factor α receptor (PDGFαR) regulatory sequences in OPCs.…”
Section: Gde2 In Oligodendroglia Does Not Impact Opc Proliferationmentioning
confidence: 84%
See 3 more Smart Citations
“…Previous studies have shown that Cre-dependent excision of exon 11 results in the complete loss of GDE2 protein expression, validating this strategy to be an effective method to ablate cellular function of GDE2 in vivo [32][33][34] . For this study, we utilized an established inducible mouse line (PDGFαR-CreER) where administration of 4 hydroxytamoxifen (4-HT) induces active Cre recombinase expression under the control of Platelet derived growth factor α receptor (PDGFαR) regulatory sequences in OPCs.…”
Section: Gde2 In Oligodendroglia Does Not Impact Opc Proliferationmentioning
confidence: 84%
“…Previous studies have shown that GDE2 is highly expressed in neurons and that during the period of developmental myelination, neuronal GDE2 stimulates the release of soluble factors that promote OL maturation without affecting OPC generation or proliferation. 26,31,34 While GDE2 function in OLs also does not affect OPC generation and proliferation, the differences in the roles of neuronal and oligodendroglial GDE2 in regulating OL maturation are striking. Neuronal and oligodendroglial GDE2 appear to have opposing functions with neuronal GDE2 promoting OL maturation and oligodendroglial GDE2 slowing the development of OLs into myelinating OLs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Wnt/β-catenin signaling pathway, also called the canonical Wnt signaling pathway, is a conserved signaling axis participating in diverse physiological processes such as proliferation, differentiation, apoptosis, migration, invasion and tissue homeostasis [1][2][3]. Increasing evidence indicates that dysregulation of the Wnt/β-catenin cascade contributed to the development and progression of some solid tumors and hematological malignancies [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%